STRATEGIC CONTENT MARKETING: A MULTI-CHANNEL ANALYSIS OF THE IMPACT ON BRAND AWARENESS, CONSUMER ENGAGEMENT, AND CONVERSION RATES IN THECONTEXT OF EVOLVING DIGITAL LANDSCAPES - Nurdin I. Muhammad; Loso Judijanto; Indah Sulistiani; Syarifuddin; Mohd Syahrin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2023)
This research explores the strategic implications of content marketing in the contemporary digital landscape, investigating its impact on brand awareness, consumer engagement, and conversion rates. Employing a multichannel analysis, the study navigates the complex interplay of diverse digital platforms and emerging technologies. Theoretical frameworks, including content marketing models and psychological dimensions, guide the exploration of consumer behavior. Technological advancements, such as artificial intelligence and virtual reality, are scrutinized for their influence on content marketing effectiveness. The study addresses existing research gaps by proposing an integrative model synthesizing brand awareness, engagement, and conversion. Methodologically, a mixed-methods approach combines quantitative surveys and analytics with qualitative insights from interviews, providing a comprehensive understanding. Findings are interpreted within the context of the literature, offering insights for both academia and practitioners. The comparative analysis with existing research contributes to refining content marketing models, acknowledging the challenges and opportunities of evolving digital landscapes.